2016
DOI: 10.1016/j.kint.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 17q12 microdeletions but not intragenic HNF1B mutations link developmental kidney disease and psychiatric disorder

Abstract: Heterozygous mutations of the HNF1B gene are the commonest known monogenic cause of developmental kidney disease. Half of patients have a deletion (approximately 1.3 Mb) of chromosome 17q12, encompassing HNF1B plus 14 additional genes. This 17q12 deletion has been linked with an increased risk of neurodevelopmental disorders, such as autism. Here we compared the neurodevelopmental phenotype of 38 patients with HNF1B-associated renal disease due to an intragenic mutation in 18 patients or due to 17q12 deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 40 publications
3
66
1
Order By: Relevance
“…Although very young, individual I1 with the intragenic HNF1B variant did not show any signs of developmental delay. Clissold and colleagues provided evidence for association of NDDs exclusively with 17q12 microdeletions but not with HNF1B intragenic variants . The predominant hypothesis for the neurodevelopmental phenotypes was haploinsufficiency of other genes encompassed by the deletion .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although very young, individual I1 with the intragenic HNF1B variant did not show any signs of developmental delay. Clissold and colleagues provided evidence for association of NDDs exclusively with 17q12 microdeletions but not with HNF1B intragenic variants . The predominant hypothesis for the neurodevelopmental phenotypes was haploinsufficiency of other genes encompassed by the deletion .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, numerous studies reported neurodevelopmental disorders (NDDs) in individuals with 17q12 microdeletions (MIM #614527) containing HNF1B . Although NDDs were considered an exclusive feature of chromosome 17q12 microdeletion syndrome (17q12DS), there are recent reports also in individuals with intragenic HNF1B alterations …”
Section: Introductionmentioning
confidence: 99%
“…35, 36 However, more recent data revealed that patients with an intragenic HNF1β mutation suffer from significantly increased renal impairment and have a reduced glomerular filtration rate (GFR) compared to patients with a whole-gene deletion. 37, 38 This indicates that in the case of intragenic HNF1β mutations, there might be an additional interfering effect of the mutant on the function of the HNF1β WT allele. The physiological effect of HNF1β binding to the Kir5.1 promoter was further investigated and confirmed in a HNF1β knockdown experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which the unique aforementioned sonographic findings are accompanied by a normal CMA result, targeted sequencing of the TCF2 gene should be performed. This approach may aid in the prenatal nephrology counseling, as mutations of TCF2 lead to isolated kidney disease without adverse neurodevelopmental outcomes …”
Section: Discussionmentioning
confidence: 99%